Molecular docking of cellobiose and cellotetraose into an endoglucanase from fusarium oxysporum - Ibrahim Ali, Noorbatcha; Hamzah, Mohd. Salleh (Journal of Pure and Applied Microbiology, 2014)
Endoglucanase is one of the three enzymes required to synergistically hydrolyze cellulose to sugar monomers which can be fermented into ethanol. Hence efforts to improve the efficiency of this enzyme, using experimental and computational approaches have been continuing vigorously. An endoglucanase, FOegI, which is same as the wellcharacterized endoglucanase I from Fusarium oxysporum (PDB ID: 3OVW) has been cloned into an appropriate expression vector, except for two mutations. As an attempt to improve the substrate binding characteristics of FOegI, computational molecular docking studies to understand the interactions in the active site regions and to suggest mutations to improve the binding characteristics was carried out in this study. The docking of ligands into active site was carried out using Lamarkian Genetic Algorithm with a fast, simplified potential of mean force (PMF) to evaluate the docking efficiency. The two substrate used in this study are cellobiose and cellotetraose. The active site is confirmed by comparing the docked structure with the available experimental structures. Cellotetraose was found to have stronger binding than cellobiose. Among the three in silico mutants tested, T224E is found to have the strongest binding energy of -530.72 +0.85with cellotetraose.